Effects of exogenous sugar on color phenotype and anthocyanin synthesis in the spathe of Zantedeschia hybrida - LÜ Chengcong; ZHANG Le; ZHAO Meng; ZHANG Zijun; HUANG Shasha; JIN Xuehua (Xibei zhiwu xuebao)
[Objective] This study aims to reveal the molecular mechanism of anthocyanin synthesis and coloration in the spathe of Zantedeschia hybrida regulated by exogenous sugars, which can provide theoretical basis for the development of postharvest preservation technology of cut flowers. [Methods] The cut flowers of pink Z. hybrida were used as materials to study the effects of glucose, mannose, mannitol, and GHG (mix of glucosamine hydrochloride and glucose) on the color phenotype, anthocyanin content, and expression of the genes related to their synthesis at 333 mmol/L, 499 mmol/L, and 666 mmol/L, respectively. [Results] (1) Treatment of glucose, mannose, and mannitol reduced spathe brightness, increased redness and chroma, and promoted anthocyanin accumulation. GHG treatment reduced spathe redness and chroma, and decreased anthocyanin accumulation. (2) 499 mmol/L mannitol promoted the expression of anthocyanin synthesis-related genes, including ZhMYB, ZhCHS, ZhCHI, ZhF3H , ZhF3'H , ZhDFR, and ZhANS, while glucose promoted the expression of six genes except ZhANS. Expression of ZhMYB, ZhCHS, and ZhCHI under GHG treatment was lower than glucose alone. [Conclusion] Appropriate amount of exogenous glucose, mannose, and mannitol can effectively promote anthocyanin accumulation in the spathe of Z. hybrida and improve color appearance. At 499 mmol/L, glucose and mannitol significantly promote the expression of anthocyanin synthesis-related genes, in which glucose may regulate the expression of ZhMYB, ZhCHS, and ZhCHI through the HXK pathway.